PELAPORAN TRANSAKSI INTERCOMPANY PADA USAHA PENGGILINGAN PADI, STUDI KASUS PADA HULLER PADI SONTY - Putra, Yosep eka; Putri, Melati; sari, Mila Yulia; Septiani, Nazila; Hazizah, Nur; ., Rahmadani; Rahmi, Mega (Sekolah Tinggi Ilmu Ekonomi Yasa Anggana Garut, 2025)
This study aims to analyze the intercompany transaction reporting system between the head office and branch units of Huller Padi Sonty, a family-owned rice milling business. Using a qualitative research method with a case study approach, data were collected through field observations, in-depth interviews with owners and managers, and examination of available financial documents. The findings reveal that intercompany reporting practices are not conducted systematically due to the absence of clear financial separation, lack of structured asset and capital records, and the unavailability of standardized accounting procedures. Transactions such as capital transfers, asset usage, and revenue recording are still performed manually without reciprocal journal entries between the head office and the branch. This condition leads to inaccuracies in preparing consolidated financial reports and creates potential discrepancies in profit calculation. The study recommends implementing a basic accounting system that includes standardized account classification, regular reconciliation, proper intercompany journal entries, and documented SOPs to ensure transparency and accuracy in intercompany reporting. These findings are expected to serve as guidance for agro-industrial in improving financial management and interunit consolidation practices.